Bifunctional Fusion Membrane‐Based Hydrogel Enhances Antitumor Potency of Autologous Cancer Vaccines by Activating Dendritic Cells. (23rd April 2022) - Ke, Yaohua; Zhu, Junmeng; Chu, Yanhong; Cen, Lanqi; Fu, Yao; Fan, Xiangshan; Shao, Jingyi; Li, Rutian; Yu, Lixia; Liu, Baorui; Liu, Qin
Abstract: Autologous tumor cell vaccine is an individualized tumor treatment strategy to elicit tumor‐specific immune responses. However, it is difficult to exert efficacy in "cold" tumors, which lack tumor‐infiltrating T cells and are not sensitive to immunotherapy. Here, a dendritic cells (DCs) activation hydrogel is constructed based on bifunctional fusion membrane nanoparticles (FM‐NPs) composed of autologous tumor cell membranes and Mycobacterium phlei membrane extracts. The FM‐NPs not only provide tumor antigens but also can activate DCs. Afterward, the FM‐NPs are loaded in an injectable alginate hydrogel together with granulocyte‐macrophage colony‐stimulating factor (GM‐CSF). GM‐CSF releases rapidly and recruits DCs to hydrogel, while FM‐NPs retain in hydrogel to continuously interconnected with DCs, enriching mature DCs loaded with tumor antigens. In the 4T1 mouse breast tumor model, this hydrogel promotes the maturation of DCs in tumor‐draining lymph nodes and induces sufficient effector memory T cells that migrate to the tumor microenvironment. This successfully converts the "cold" tumors to "hot", thus exerting a significant antitumor effect synergized with the PD‐1 antibody. It is also verified the inhibitory effect of FM‐NPs using human gastric cancer organoids. Altogether, these findings demonstrate the application potential for the bifunctional fusion membrane‐based hydrogel as an autologous tumor vaccine by activating DCs. Abstract : An injectable bifunctional fusion membrane‐based hydrogel acts as an in situ dendritic cells (DCs) activation nodule. It provides the immune system with a large number of mature DCs loaded with tumor antigens, which is beneficial to increasing the proportion of effector memory T cells in tumors and reversing immune desertification. This hydrogel provides a feasible strategy for the enhancement of clinical autologous cancer vaccines.